The Impact of the Quizlet App on Students' Mufradât Mastery: An Experimental Study - N. Hula, Ibnu Rawandhy; Arrashedy, Yousif Abdelmannan Mohamed Godat; Lahay, Mohamad; I. Miolo, Mukhtar; Damhuri, Damhuri; Sakka, Abdullah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
This research is motivated by the observation that 10th-grade students at MAS Al-Huda in Gorontalo City have low mastery of mufrad